(untitled) (Global Journal of Human-Social Science, 2023)
Democracy is a regime by which the people impose their veto by choosing their representatives for a defined time on the basis of a social program that adapts to the socio-political realities of the primary sovereign In the case of the DRC we are in fact proposing the foundation of the Congolese state which must start from democracy to impose a state with strong and enlightened leadership authoritarianism a bit like what happened in Russia with Putin and in Mao s China because for us not only does it correspond to a Western-type regime corresponding to the way of life the understanding of things and adaptations to Western realities and behavior but it is the result or the reflection of the States already mature developed which have already laid the foundations for development is where state institutions and entities are seated A State where the leaders and the people are well prepared educated in development and democratic values by defining its prerogatives its needs to love and protect national interests